Predictive value of S100A4 in eosinophilic chronic rhinosinusitis with nasal polyps - Zou, Shangchu; Huang, Zhicheng; Wu, Jinpeng (Frontiers in Surgery, 2022)
Objective: S100A4 is a pro-inflammatory mediator which has been implicated in airway inflammatory diseases. However, its role in chronic rhinosinusitis with nasal polyps (CRSwNP) remains unclear. The purpose of this study is to determine the expression of S100A4 and evaluate its potential value in distinguishing its endotypes. Methods: Sixty CRSwNP patients, 30 chronic rhinosinusitis without nasal polyps (CRSsNP) patients, and 30 healthy controls (HC) were enrolled in this study, and serum and tissue samples were collected. Serum and tissue S100A4 levels were detected by enzyme-linked immunosorbent assay, reverse transcription-polymerase chain reaction, western blotting and immunofluorescence. Their clinical values in predicting postoperative recurrence of CRSwNP were evaluated by multivariate analysis and ROC curves. Results: Serum levels of S100A4 were notably increased in the CRSwNP group than the CRSsNP and HC groups (p<0.05), and positively correlated with tissue and peripheral eosinophil count and percentage (p<0.05). The serum S100A4 concentrations were significantly elevated in the Eos CRSwNP group in comparison with the non-Eos CRSwNP group (p< 0.05). Multivariate analysis and ROC curve presented that serum S100A4 levels were associated with CRSwNP endotypes. Additionally, tissue S100A4 mRNA and protein levels were significantly enhanced in the CRSwNP group than the HC group and CRSsNP group, especially in the Eos CRSwNP group. Conclusion: Our results demonstrated that the S100A4 expression was increased in CRSwNP patients and associated with the endotypes. S100A4 could be a serologic biomarker for evaluating tissue eosinophilic inflammation and predicting endotypes in CRSwNP patients.